Antifragile eaudiobook Things that gain from disorder. - Taleb, Nassim Nicholas (Incerto, 2012)
Antifragile is a standalone book in Nassim Nicholas Taleb’s landmark Incerto series, an investigation of opacity, luck, uncertainty, probability, human error, risk, and decision-making in a world we don’t understand. The other books in the series are Fooled by Randomness, The Black Swan, and The Bed of Procrustes . Nassim Nicholas Taleb, the bestselling author of The Black Swan and one of the foremost thinkers of our time, reveals how to thrive in an uncertain world.   Just as human bones get stronger when subjected to stress and tension, and rumors or riots intensify when someone tries to repress them, many things in life benefit from stress, disorder, volatility, and turmoil. What Taleb has identified and calls “antifragile” is that category of things that not only gain from chaos but need it in order to survive and flourish.    In The Black Swan, Taleb showed us that highly improbable and unpredictable events underlie almost everything about our world. In Antifragile, Taleb stands uncertainty on its head, making it desirable, even necessary, and proposes that things be built in an antifragile manner. The antifragile is beyond the resilient or robust. The resilient resists shocks and stays the same; the antifragile gets better and better.   Furthermore, the antifragile is immune to prediction errors and protected from adverse events. Why is the city-state better than the nation-state, why is debt bad for you, and why is what we call “efficient” not efficient at all? Why do government responses and social policies protect the strong and hurt the weak? Why should you write your resignation letter before even starting on the job? How did the sinking of the Titanic save lives? The book spans innovation by trial and error, life decisions, politics, urban planning, war, personal finance, economic systems, and medicine. And throughout, in addition to the street wisdom of Fat Tony of Brooklyn, the voices and recipes of ancient wisdom, from Roman, Greek, Semitic, and medieval sources, are loud and clear.   Antifragile is a blueprint for living in a Black Swan world.   Erudite, witty, and iconoclastic, Taleb’s message is revolutionary: The antifragile, and only the antifragile, will make it. Includes a bonus PDF of supplemental charts and graphics Please note that that bleeps in the audio are intentional and are as written by the author. No material is censored, and no audio content is missing. Praise for Antifragile   “Ambitious and thought-provoking . . . highly entertaining.” — The Economist   “A bold book explaining how and why we should embrace uncertainty, randomness, and error . . . It may just change our lives.” — Newsweek   “Revelatory . . . [Taleb] pulls the reader along with the logic of a Socrates.” — Chicago Tribune   “Startling . . . richly crammed with insights, stories, fine phrases and intriguing asides . . . I will have to read it again. And again.” —Matt Ridley, The Wall Street Journal   “Trenchant and persuasive . . . Taleb’s insatiable polymathic curiosity knows no bounds. . . . You finish the book feeling braver and uplifted.” — New Statesman   “Antifragility isn’t just sound economic and political doctrine. It’s also the key to a good life.” — Fortune ...